Hereditary breast cancer syndromes and genetic testing. Issue 1 (7th November 2014) - Rich, Thereasa A.; Woodson, Ashley H.; Litton, Jennifer; Arun, Banu
<x xml:space="preserve">Abstract</x> Only 5% of breast cancers are explained by highly penetrant multisystem autosomal dominant hereditary disorders. Though another 20–30% has a familial presentation, the genetic and other etiologies are still not well understood. Genetic testing is now widely available and multiple professional societies have published guidelines for testing and management. Genetic testing trends include utilization of multi‐gene panels that take advantage of next‐generation sequencing as well as testing for low‐ and moderate‐penetrance susceptibility genes. J. Surg. Oncol. 2015 111:66–80. © 2014 Wiley Periodicals, Inc.